Crystallization and preliminary X-ray crystallographic analysis of human FAF1 UBX domain - Kang, Wonchull (International Union of Crystallography, 2010)
Fas-associated factor 1 (FAF1) is a multifunctional pro-apoptotic protein that is involved in Fas-mediated apoptosis, NF-κB signalling and the ubiquitin–proteasome pathway. In the ubiquitin–proteasome pathway, FAF1 binds to the N domain of p97/VCP, a molecular chaperone that acts in complex with the proteasome, through its C-terminal UBX domain and inhibits the proteasomal protein-degradation process. In an effort to elucidate the structural basis of the function of FAF1 in modulating p97/VCP activity related to proteasomal protein degradation, crystallographic analysis of the FAF1 UBX domain and the p97/VCP N domain was initiated. Following the recently reported crystallization of the FAF1 UBX domain bound to the p97/VCP N domain, the unbound FAF1 UBX domain was also crystallized for purposes of structural comparison. X-ray data were collected to 3.00 Å resolution and the crystals belonged to space group F4(1)32, with unit-cell parameters a = b = c = 176.40 Å. The Matthews coefficient and solvent content were estimated to be 3.04 Å(3) Da(−1) and 59.5%, respectively, assuming that the asymmetric unit contained two molecules of the UBX domain, which was subsequently confirmed by molecular-replacement calculations.